Penyuluhan Kesehatan Tentang Penguatan Imun Tubuh Untuk Mencegah Tertularnya Virus Covid 19 Kepada Pedagang Pasar Pelas - Della Ika Mardiana; Faiz Amiruddin (LP3M IAIFA Kediri, 2021)
Corona Virus Disease 2019 or better known as Covid-19 has become a worldwide pandemic. This disease is caused by the abbreviated Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2). Now the virus is spreading rapidly and is very dangerous. Therefore, it is necessary to know the role of the body's immune system in order to prevent contracting the virus, the body's immune system is a defence or immune system that has a role in recognizing and destroying foreign objects or abnormal cells that harm the body. The body's immune system is divided into two, namely specific immunity and non-specific immunity. And how to strengthen the body's immune naturally by eating nutritious foods, reducing alcoholic beverages, doing regular exercise, sleeping regularly, reducing stress, limiting sugar consumption, staying hydrated, and finally washing your hands regularly. Researchers conduct health education about strengthening body immunity to market traders because a market is a place where many people gather and usually traders rarely take care of their health because they are busy, especially in terms of sports. Pelas Market, which is located in Pelas Village, Kras District, Kediri Regency, is a research centre because the market is far from urban areas and the traders who come from Blitar and Tulungagung also because the market is located in the south of Kediri Regency and there are still many traders who do not know about body immunity in detail.